THE EFFECT OF WORK MOTIVATION, WORK CULTURE, AND RESPONSIBILITY ON EMPLOYEE PERFORMANCE AT THE GALANG SUB-DISTRICT OFFICE IN BATAM - Saputra, Wahyudi Andika; Sabri, Sabri; Sudianto, Sudianto (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
This study aims to analyze the influence of work motivation, work culture, and responsibility on employee performance at the Galang District Office, Batam City. The study sample included all 91 employees using census techniques. Data collection methods included observation, interviews, questionnaires, and literature reviews. Data analysis used validity and reliability tests, as well as multiple regression to examine the influence of independent variables on the dependent variable. The results showed that work motivation contributed the most significant amount of 38.7% to employee performance, followed by work culture at 33.2% and responsibility at 28.1%. These three variables simultaneously had a significant effect on employee performance, as indicated by a calculated F value > the F table value. This study shows that improving employee performance does not depend solely on one factor, but rather on a balanced combination of work motivation, work culture, and responsibility. This finding emphasizes the importance of implementing an integrated human resource management strategy to improve the quality of public services at the Galang District Office.